Incorporating Overconfidence into Real Option Decision-Making Model of Metal Mineral Resources Mining Project - Jian-bai Huang; Na Tan; Mei-rui Zhong (Discrete Dynamics in Nature and Society)
As for uncertainties and decision-makers’ overconfidence psychological bias, overconfidence has been incorporated into real option decision-making model of metal mineral resources mining to estimate its effect on decision-making of the project and thus a behavioral real option decision-making model of metal mineral resources mining based on overconfidence has been established. Furthermore, numerical simulation and sensitivity analysis have been conducted to verify the practicality of the model. Results show that model in this paper has greatly changed trigger value and option value of mineral resources mining project compared with traditional real option model, thus greatly changing optimal decision results. Incorporating overconfidence into real option decision-making model of metal mineral resources development is a crucial extension of project evaluation theory.